Long-term follow-up of patients undergoing tibialis posterior transfer: Is acquired pes planus a complication?. (March 2018) - Pecheva, Mira; Devany, Adam; Nourallah, Basil; Cutts, Steven; Pasapula, Chandra
Highlights: A total of 10 patients were identified over a 10 year period as having undergone a TP transfer. No patients developed planovagus or symptoms of early tibialis dysfunction syndrome as there were no symptoms of valgus impingement pain or medial retromalleolar pain on follow up. There was no significant difference for calcaneal pitch, Meary's angle and the talo-calcaneal angle. Talonavicular angles did, however, significantly improve as a result of cavus correction and there was no increase in uncoverage. Abstract: In this retrospective study, a series of 10 elective patients treated with transfer of the tibialis posterior (TP) tendon for pes cavus and drop foot are described. Since TP transfer completely subtracts the role of this tendon, this cohort of patients provides an opportunity to examine the consequences of tibialis posterior (TP) deficiency. After a mean follow up period of 44.7 months, only one patient showed evidence of strain in the spring ligament but none of the patients in this series developed clinical or radiological evidence of planovalgus deformity. The authors conclude that planovalgus deformity is not an inevitable sequelae of TP Tendon transfer and that established theory underestimates the role of static soft tissue restraints such as spring ligament in hindfoot stability.